Delineation of the clinical and radiological features of Stuve–Wiedemann syndrome childhood survivors, four new cases and review of the literature. Issue 3 (11th December 2020) - Siccha, Sofía M.; Cueto, Anna María; Parrón‐Pajares, Manuel; González‐Morán, Gaspar; Pacio‐Miguez, Marta; Del Pozo, Ángela; Solís, Mario; Rodriguez‐Jimenez, Carmen; Caino, Silvia; Fano, Virginia; Heath, Karen E.; García‐Miñaúr, Sixto; et al.
Abstract: Stuve–Wiedemann syndrome (SWS; MIM 601559) is a rare autosomal recessive disease caused by mutations in the leukemia inhibitor factor receptor gene ( LIFR ). Common clinical and radiological findings are often observed, and high neonatal mortality occurs due to respiratory distress and hyperthermic episodes. Despite initially considered as a lethal disorder during the newborn period, in recent years, several SWS childhood survivors have been reported. We report a detailed clinical and radiological characterization of four unrelated childhood SWS molecularly confirmed patients and review 22 previously reported childhood surviving cases. We contribute to the definition of the childhood survival phenotype of SWS, emphasizing the evolving phenotype, characterized by skeletal abnormalities with typical radiological findings, distinctive dysmorphic features, and dysautonomia. Based on the typical features and clinical course, early diagnosis is possible and crucial to plan appropriate management and prevent potential complications. Genetic confirmation is advisable in order to improve genetic counseling to the patients and their families.